No one to someone : The story of go girl! Magazine and friends / By Nina Morah ; penyunting, Nurjannah Intan dan Ikhdah Henny - NINA MORAH; Nurjannah Intan; Ikhdah Henny (B-First, 2013)
188 hlm. ilus. 20 cm. [3 ekls.]